DEVELOPMENT OF SIMULATION TRAINING FOR THE CARE OF ADOLESCENTS WITH ARTERIAL HYPERTENSION - Tillabaeva Akida Aripovna. (Western European Studies, 2024)
Today, scientific research in all directions is being conducted, including in the field of medicine. The development of medicine makes it possible to find solutions to incurable diseases of patients, to treat them with the most accurate diagnoses. This article provides comments on modern medicine and its prospects. Simulation training was also developed for the care of adolescents with arterial hypertension
Keywords: Health; doctor; rural medical centers; health